AB0467 IMPROVED DISEASE CONTROL OF SYSTEMIC LUPUS ERYTHEMATOSUS AND ITS POSSIBLE ASSOCIATION WITH AGGRESSIVE USE OF IMMUNOSUPPRESSANTS. (June 2019) - Imaizumi, Chihiro; Inoue, Yuki; Kagtagiri, Takaharu; Takenaka, Sayaka; Ito, Hideki; Hirata, Ayako; Ogura, Takehisa; Kameda, Hideto
Abstract : Background: The outcome of patients with systemic lupus erythematosus (SLE) has considerably improved in recent decades. Objectives: The aim of this retrospective study was to examine whether the disease control has been actually improved and its possible association with the altered balance between the use of immunosuppressants and glucocorticoids. Methods: We enrolled SLE patients who visited Toho University Ohashi Medical Center during 2012-2017 (Group A, 79 patients), and compared them with patients during 1999-2003 (Group B, 68 patients; not overlapping with Group A). All the patients met the American College of Rheumatology 1997 revised criteria for SLE classification. Patient backgrounds, the dose of glucocorticoids and the use of immunosuppressants at the times of SLE onset and disease flare were reviewed from the medical records. The disease flare was defined as a new BILAG 2004 A or B score in at least one system. Results: The age at disease onset and sex, as well as the presence of lupus nephritis and serositis were comparable between 2 groups, although central nervous system manifestations were less frequent in Group A (7% versus 19% in Group B, p=0.04). The average number of flare per person-year was significantly reduced in Group A than Group B (0.26 versus 0.4, respectively, p<0.01). In the initial treatment, the median dosage of oral prednisolone was equivalent in both groups (30 mg day, p=0.64), while the total glucocorticoid dosage in the initial 16 weeks was significantly reduced in Group A (1, 960 mg prednisolone equivalent versus 2, 913 mg in Group B, p=0.01). And the inclusion rate of immunosuppressants in the initial SLE treatment was significantly higher in Group A (43% versus 6% in Group B, p<0.01). Further, upon disease flare, the dose of prednisolone for it was significantly lower in Group A (6.5 mg/day versus 14 mg/day in Group B, p<0.01) and the rate of introduction or alteration of immunosuppressants were significantly higher in Group A (81% versus 24% in Group B, p<0.01). Infection rates were similar between the groups (p=0.44). Conclusion: Aggressive use of immunosuppressants in recent years resulted in the reduction of the rate of SLE flare as well as that of cumulative glucocorticoid dosage. References: [1] Bernatsky S, et al. Arthritis Rheum 2006; 54: 2550-7 [2] Lee Y, et al. Lupus 2016; 25: 727-34. [3] Guillermo R.I. Rheumatology 2012; 51: 1145-53 [4] Ugarte A, et al. Lupus 2011; 4: 423 [5] Pepper R, et al. Nephrol Dial Transplant 2009; 24: 3717-23. [6] Saag KG, et al. Am J Med 1994;96: 115-23 [7] Ruiz-Irastorza G, et al. Arthritis Res Ther 2009;11:R109. Disclosure of Interests: Chihiro Imaizumi: None declared, Yuki Inoue: None declared, Takaharu Kagtagiri: None declared, Sayaka Takenaka: None declared, Hideki Ito: None declared, Ayako Hirata: None declared, Takehisa Ogura: None declared, Hideto Kameda Grant/research support from: AbbVie, Asahi Kasei Pharma, Astellas, Chugai, Eisai, GlaxoSmithKlein, Mitsubishi-Tanabe, Novartis, Consultant for: AbbVie, Eli Lilly, Novartis, Speakers bureau: AbbVie, Asahi Kasei Pharma, Bristol-Myers, Chugai, Eli Lilly, Janssen, Mitsubishi-Tanabe, Novartis, Pfize